Design And Control System of Automatic Control System of Coal Flow on Belt Conveyor Installation - Bayu Pranoto; Chandra Gunawan; Hilmi Iman Firmansyah; Hangga Wicaksono; Andhika Angger Nugraha; Muhammad Trifiananto (Mekanika: Majalah Ilmiah Mekanika, 2021)
In this study, we discuss a case where the installation of a belt conveyor, which was initially only one line, was then made a new branch that supplies coal to other power generating units. Equitable capacity distribution and continuity of coal distribution are the main focus of this study. Therefore, an automatic control system of coal flow divider on belt conveyor installation was designed. The working principle of this coal flow splitting system is to control the movement of the straight blade plow that directs the flow of coal to each unit at a particular time and continuously. Straight blade plows in the form of steel metal plate with a thickness of about 10 mm in which one end is connected to the end of the pneumatic cylinder. The automatic control system of the coal flow divider in belt conveyor installation was designed using CX-Programmer and CX-Designer applications. CX-Programmer serves to create automatic control logic concepts. While the CX-designer functions to create a Human Machine Interface (HMI). The results of this study are in the form of control logic lines that can be applied to Programmable Logic Control (PLC) devices and Human Machine Interface (HMI) equipment.